Development of capabilities in Western professional services firms internationalising in fast-growing economies - Villeneuve-Moore, Amelie (Cranfield University, 2013)
This research was inspired by both a practical and a theoretical challenge: how Western professional services firms (PSFs) internationalise into fast-growing economies. The research contributes to theory by proposing a model comprising groups of capabilities, within which different combinations of capabilities, labelled types, develop or change depending on the context and service offering. Eight capabilities and two types have been identified as important to firms internationalising into fast-growing economies. PSFs that deliver standardised offerings appear to perform well when they have Type A properties of the eight capabilities. PSFs that offer idiosyncratic and context-specific services appear to perform well when they have Type B properties of the eight capabilities. Some evidence supporting the concept of dynamic capabilities which renew, regenerate or refresh capabilities has been found. The research addresses a gap in three overlapping theoretical areas: internationalisation, capabilities and the context of professional services firms. This context continues to be important to practitioners as GDP growth in Western countries remains low, relative to the fast-growing economies, thereby presenting the need for firms to grow into these economies in order to survive. Much of the capabilities literature analyses the effects of a given capability, but has focused less on groups of capabilities. Finally the professional services industry is reported to be a leading growth industry, with an important impact on other industries; however it remains relatively under-researched. I have researched nine firms, using a case study approach to derive a theoretical model comprising groups of capabilities identified through the first two projects, which was then refined and examined over different time periods in the final project.